Potensi Gastronomi sebagai Daya Tarik wisata di Coklat Monggo Yogyakarta - Febry Fatimah Azzahra; Rigy Dyantika; Asep Parantika (Peneliti.net, 2023)
Chocolate monggo has a tourist attraction in the form of a gastronomic destination located in Kota Gede, Yogyakarta. Monggo chocolate is a processed chocolate product that is produced and marketed centrally in Yogyakarta for souvenirs. The purpose of this research is to find out the Gastronomic Potential as a Tourist Attraction in Chocolate Monggo Yogyakarta. This research design uses data collection in the form of a literature study with a qualitative descriptive method through observation techniques. The results of this study indicate that the factors that influence tourists visiting Chocolate Monggo are caused by tourist attractions by exploring the chocolate factory, knowing the history of its establishment, how to make praline chocolate and tasting the various types of chocolate available.